The digital maturity of supply chain technology in South Africa - Nkwenkwe, Monde (University of the Witwatersrand, Johannesburg, 2024)
“The most profound technologies are those that disappear... They weave themselves into the fabric of everyday life until they are indistinguishable from it” wrote computer scientist and visionary Mark Weiser nearly 25 years ago in his essay The Computer for the 21st Century (Facchini, 2020, p.39) Agility, resilience, and reliability have emerged as increasingly vital factors in supply chain management, particularly in navigating the complexities of a digitalized landscape. The objective of the study is to assess the digital maturity of supply chain technologies in South Africa, contrasting them with global maturity standards. The study's motivation stems from the need to comprehend the capacity of supply chain networks to meet the growing demand driven by the adoption of e- commerce and other external factors affecting the supply chain. The study on the digital maturity of supply chain technology in South Africa is crucial as it provides a comprehensive assessment of how advanced and integrated digital technologies are within the country's supply chain sector. It highlights the current state of technological adoption, identifying areas where South African supply chains excel and where they lag. This understanding is vital for enhancing operational efficiency, competitiveness, and resilience against disruptions. Furthermore, the study's insights can inform policy making, guide investments, and support businesses in adopting best practices, ultimately contributing to economic growth and sustainability by optimizing resource use and reducing operational costs. Employing a qualitative research approach, the study explores patterns of technology adoption in the supply chain and the resulting maturity of the technology, as per the propositions. The conceptual framework provides a clear delineation of the evolution from a traditional supply chain to a digitalized value chain, integrating technology across various segments of the supply chain network. Furthermore, it elucidates the integration of 4IR technologies such as IoT, robotics, cloud services, and big data analytics and the resultant impact on the efficiencies and effectiveness of the supply chain. Data was gathered through both focus group sessions and individual interviews involving a diverse range of supply chain experts, including individuals from sales, consultancy, implementation, and support teams. The primary finding indicates a consensus in adoption between the global patterns and the south African context. However, it is evident that the maturity level of technology utilization remains in its infancy stage in South Africa. Resilience of the supply chain is limited by the siloed implementation approach of technologies that do not function across the full value chain and data inconsistencies across the value chain prohibiting end to end visibility for efficient fulfilment of consumer requirements. Mature digital implementation of supply chain technology can significantly impact businesses in a positive manner by enhancing efficiency, competitiveness, and strategic decision-making
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Supply chain; Digital maturity; E-commerce; Maturity models; Digital technologies; UCTD; SDG-8: Decent work and economic growth; SDG-9: Industry, innovation and infrastructure